Critical Discourse Analysis of Television News Coverage on the Relocation of Indonesia’s Capital City - Adiputra, Andika Vinianto; Agustin, Herlina; Hijriah, Moch. Rizqi (Jurnal Kajian Jurnalisme, 2024)
The new phase of the State Capital Relocation (IKN) began in 2019, after President Joko Widodo inaugurated that Indonesia's capital would move to East Kalimantan. The relocation has been ongoing since then and has entered the infrastructure development stage. However, beyond the grandeur of the IKN construction, many aspects have been affected. This research aims to understand how the examined media construct discourse on capital relocation. This research employs a qualitative method, utilizing Norman Fairclough's critical discourse analysis model. Discourse analysis is conducted through three stages: text analysis, discourse practice analysis, and sociocultural analysis.  Data collection methods were carried out using observation techniques, documentation studies through television media reporting, and in-depth interviews with informants representing Trans TV, Kompas TV, SCTV and NET. The research results in the text dimension indicate that the majority of the reporting is not in favour of the government's decision to relocate the capital because it is considered rushed in planning and has various negative impacts. In the discourse practice dimension, the reporting is heavily influenced by the media's socio-economic status (SES) in shaping the discourse. In the sociocultural dimension, it is shown that the capital relocation is one of the political strategies, and there is disagreement among various parties regarding the relocation. Therefore, the researcher suggests that the examined media should present balanced reporting and provide a balanced perspective in their coverage. Furthermore, caution is needed from the media to avoid being influenced by external media domination, ensuring that the information reported is accountable and prioritizes the public interest.